Hindrance of 1, 4-dioxane biodegradation in microcosms biostimulated with inducing or non-inducing auxiliary substrates. (1st April 2017) - Li, Mengyan; Liu, Yuanyuan; He, Ya; Mathieu, Jacques; Hatton, James; DiGuiseppi, William; Alvarez, Pedro J.J.
Abstract: A microcosm study was conducted to assess two biostimulation strategies (relative to natural attenuation) to bioremediate 1, 4-dioxane contamination at a site in west Texas. Dioxane concentrations were relatively low (<300 μg/L), which represents a potential challenge to sustain and induce specific degraders. Thus, biostimulation was attempted with an auxiliary substrate known to induce dioxane-degrading monooxygenases (i.e., tetrahydrohyran [THF]) or with a non-inducing growth substrate (1-butanol [1-BuOH]). Amendment of 1-BuOH (100 mg/L) to microcosms that were not oxygen-limited temporarily enhanced dioxane biodegradation by the indigenous microorganisms. However, this stimulatory effect was not sustained by repeated amendments, which might be attributed to i) the inability of 1-BuOH to induce dioxane-degrading enzymes, ii) curing of catabolic plasmids, iii) metabolic flux dilution and catabolite repression, and iv) increased competition by commensal bacteria that do not degrade dioxane. Experiments with the archetype dioxane degrader Pseudonocardia dioxanivorans CB1190 repeatedly amended with 1-BuOH (500 mg/L added weekly for 4 weeks) corroborated the partial curing of catabolic plasmids (9.5 ± 7.4% was the plasmid retention ratio) and proliferation of derivative segregants that lost their ability to degrade dioxane. Addition of THF (300 μg/L) also had limited benefit due to competitive inhibition; significant dioxane degradation occurred only when the THF concentration decreased below approximately 160 μg/L. Overall, these results illustrate the importance of considering the possibility of unintentional hindrance of catabolism associated with the addition of auxiliary carbon sources to bioremediate aquifers impacted with trace concentrations of dioxane. Graphical abstract: Highlights: Biostimulation with auxiliary substrates temporarily enhances dioxane degradation. But auxiliary carbon sources can have counterproductive long-term consequences. Inducing substrates support growth of degraders but exert competitive inhibition. Non-inducing growth substrates can cure plasmids causing loss of degradation capacity.